Öryggishlutverk lögreglu - Birgir Jónasson (Nordicum-Mediterraneum, 2024)
This article addresses the security role of the police according to paragraph 2 (a) in Article 1 of the Icelandic Police Act no. 90/1996 in the aspect of police law. The general role of the police is discussed, and each section of the provision is defined further. The multiple means of the security role are illuminated in terms of other judicial rules, how the role is practised and how Icelandic courts have interpreted the provisions. The article is a part of the author’s research on Icelandic police law. The issue is also based on the author’s academic approach to teaching police law at the University of Akureyri.